Strategy for Improving Teacher Quality Based on MGMP to Enhance Professional Competence in Elementary Schools in Jeumpa District, Bireuen Regency - Munawar Munawar; Siraj Siraj (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
Enhancing teacher professionalism is a crucial objective for improving educational quality, especially in elementary education systems that are encountering rising expectations for pedagogical effectiveness, curriculum adaptability, and technological integration. The Subject Teacher Consultation Forum (Musyawarah Guru Mata Pelajaran/MGMP) serves as a collaborative professional development platform aimed at enhancing teacher competency and instructional efficacy. This study examines measures to enhance teacher quality via MGMP activities to improve professional competence in public elementary schools in Jeumpa District, Bireuen Regency. The research utilised a descriptive quantitative methodology supplemented by qualitative data gathered from interviews, observations, and documentation. The data were examined via descriptive statistical methods and interpretative qualitative analysis. The results indicate that MGMP-based programs substantially improve teachers' professional competence, especially in pedagogical understanding, instructional planning, and curriculum execution. Nonetheless, certain structural and operational limitations were recognised, including restricted teacher involvement, inadequate program continuity, and insufficient institutional backing. The study finds that fortifying MGMP governance, augmenting teacher involvement, and guaranteeing sustainable institutional support are crucial for optimising teacher professional development and raising educational quality.